The Effect of Tax Extensification and Intensification on Regional Tax Revenue at the Regional Revenue Management Agency of Sumedang Regency - Mariana, Syafira (LPPM Universitas Sebelas April, 2024)
Extensification and Intensification are government efforts to increase regional tax revenues. Based on the phenomenon that occurs at BAPPENDA Sumedang Regency, there are still many taxpayers who have not carried out their obligation to pay regional taxes according to the regulations. The aim of this research is to find out the influence of Tax Extensification and Intensification activities on Regional Tax Revenue at BAPPENDA Sumedang Regency. The research method used in preparing this thesis is a descriptive analysis method with a secondary data survey type of monitoring. The data collection technique was in the form of a questionnaire distributed to 26 Sumedang Regency BAPPENDA employees. The data analysis techniques used in this research are multiple regression techniques, correlation analysis, coefficient of determination, t test and f test. Testing this statistical analysis using the help of IBM SPPS 17. Then the results of this analysis are that Tax Extensification and Intensification influence Regional Tax Revenues partially or simultaneously, and the value of the influence of Taxation Extensification and Intensification on Sumedang Regency Regional Tax Revenues is 83.1% and the remaining 16.9% is influenced by other factors. Based on the results of the research, the researcher provided suggestions to BAPPENDA Sumedang Regency to further increase the internal collaboration of the special Extensification team and to intensify outreach and increase the number of Human Resources so that the implementation of Regional Tax Extensification and Intersification runs more optimally